2007
DOI: 10.1103/physrevb.76.205113
|View full text |Cite
|
Sign up to set email alerts
|

Full band structure LDA andkpcalculations of optical spin-injection

Abstract: We present a study of optical electron spin-injection ͑optical orientation͒ in the bulk semiconductors GaAs, Si, and CdSe from direct optical excitation with circularly polarized light. For GaAs and Si, we compare pseudopotential calculations with calculations of a recent full-zone k • p model. For GaAs, we find that there can be up to 30% spin-injection at energies well above the band gap. For Si, which has very weak spin-orbit coupling, we find that there can be up to 30% spin polarization from direct transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 52 publications
(58 reference statements)
4
92
0
Order By: Relevance
“…39 We prefer the present k · p approach over an ab initio treatment for two main reasons. First, computational times, both overhead and per k point, are significantly less in a k · p calculation than in even a local-densityapproximation calculation.…”
Section: Computational Detailsmentioning
confidence: 99%
“…39 We prefer the present k · p approach over an ab initio treatment for two main reasons. First, computational times, both overhead and per k point, are significantly less in a k · p calculation than in even a local-densityapproximation calculation.…”
Section: Computational Detailsmentioning
confidence: 99%
“…They demonstrated that the degree of spin polarization (DSP) is 50% (−83.3%) for electrons (holes) at the direct gap energy threshold (i.e., 0.89 eV), as expected by considering the atomic-like character of the zone center energy levels. It was also shown that the spectral dependence of the electronic DSP, as summarized in the left panel of Figure 4 mimics the one of GaAs [130] and decreases at the onset of the absorption from the SO band. This behavior was shown to be mainly caused by the LH rather than the commonly argued transitions related to the SO band [129].…”
Section: Optical Investigations Of the Spin Physics Of Group IV Matermentioning
confidence: 70%
“…with Φ 0 being the photon flux into the semiconductor, P(hν) the initial polarization of the photo-generated electrons [47,48] and α(hν) the absorption coefficient [46]. Figure 4 also shows the comparison between the experimental data and the ISHE signal obtained by using this simplified model (dashed lines).…”
Section: Photon Energy Dependence Of the Optically-induced Inverse Spmentioning
confidence: 98%
“…The electron mobility at the doping density of our samples was assumed equal to µ Ge = 3560 cm 2 ·V −1 ·s −1 and µ GaAs = 2051 cm 2 ·V −1 ·s −1 [45], corresponding to a diffusion coefficient D e = µk B T/e approximately equal to 89 cm 2 ·s −1 for Ge and 50 cm 2 ·s −1 for GaAs, respectively. The generation term was explicitly accounted for by considering the semiconductor absorption coefficient [46] and the spin polarization theoretically expected for illumination with 100% circularly polarized light [47,48], while carrier recombination was described by the Shockley-Read term [49] and spin relaxation by a decay time τ s . The model portrays the spatial distribution of spins residing at the Γ valley for GaAs and at the L valleys for Ge under the approximation that all the electrons are thermalized.…”
Section: Photon Energy Dependence Of the Optically-induced Inverse Spmentioning
confidence: 99%